2017
DOI: 10.1089/zeb.2017.1440
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transit Time and Cortisol-Mediated Stress in Zebrafish

Abstract: Intestinal motility, the spontaneous and rhythmic smooth muscle contraction, is a complex process that is regulated by overlapping and redundant regulatory mechanisms. Primary regulators intrinsic to the gastrointestinal tract include interstitial cells of Cajal, enteric neurons, and smooth muscle cells. Extrinsic primary regulators include the autonomic nervous system, immune system, and the endocrine system. Due to this complexity, a reductionist approach may be inappropriate if the ultimate goal is to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The SR4G reporter demonstrated that handling zebrafish larvae during the execution of the intestinal transit assay induces an increase in cortisol secretion (Brady et al 2017) and in vivo confirmed the interaction between methylmercury, an environmental contaminant, and the Gr, previously suggested by molecular dynamics simulations. Moreover, this interaction was found to have a role in the developmental neurotoxic effects determined by this molecule (Spulber et al 2018).…”
Section: In Vivo Visualization Of Gc/gr Transcriptional Activity In Zsupporting
confidence: 78%
“…The SR4G reporter demonstrated that handling zebrafish larvae during the execution of the intestinal transit assay induces an increase in cortisol secretion (Brady et al 2017) and in vivo confirmed the interaction between methylmercury, an environmental contaminant, and the Gr, previously suggested by molecular dynamics simulations. Moreover, this interaction was found to have a role in the developmental neurotoxic effects determined by this molecule (Spulber et al 2018).…”
Section: In Vivo Visualization Of Gc/gr Transcriptional Activity In Zsupporting
confidence: 78%
“…[ 136 ] In smooth muscle, spontaneous rhythmic muscular contraction is regulated for supporting intestinal motility. [ 137 ] In response to intestinal distension, active contractile forces are generated by intestinal wall motions incorporating coordinated circular and longitudinal muscular motions. [ 138 ] Therefore, the scaffold should be subjected to the same mechanical environment following the type of the engineered tissue during the experimental research. Universalizing PGA scaffolds in varied fields of tissue engineering application Besides, the applicability of the PGA scaffold should be made universal that it can be applied to most of the human tissues.…”
Section: Potential Future Work and Their Associated Challengesmentioning
confidence: 99%
“…yellow-legged gull, Larus michahellis: Noguera et al, 2018) and fish (rainbow trout: Rosengren et al, 2018) it has been reported that hormonal manipulation of the HPA-HPI axis can significantly alter intestinal microbiota. However, it is difficult to make generalisations given the small number of species assessed, as, for instance, no effects of HPI manipulation were observed in the zebrafish gastrointestinal tract (Brady et al, 2017).…”
Section: Central Regulation Of Gut Functionsmentioning
confidence: 99%